The connection of the Ions and electrons in the Earth’s central plasma sheet to the solar wind - Espinoza, Jose M.; Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2025)
The simple problems of the solar wind number density driving the plasma sheet number density and the solar wind speed driving the plasma sheet temperature are examined. To ensure that the central plasma sheet is studied, 1017 current sheet crossings in the plasma sheet are collected from 10.8 RE to 76.9 RE downtail, and 3-s resolution ion and electron measurements from THEMIS-B and THEMIS-C are compared with time-lagged solar wind number densities and speeds. The central plasma sheet measurements are taken from the solar minimum years of 2007–2009. Three correlation methods are used: (1) Pearson (univariate) linear correlations; (2) multivariate linear correlations; (3) canonical correlation analysis. For both ions and electrons, knowing the solar wind speed adds insignificant information to the solar wind density versus plasma sheet density correlations. Likewise, for both ions and electrons, knowing the solar wind density adds insignificant information to the solar wind speed versus plasma sheet temperature correlations. The standard two problems (1) the density of the solar wind driving the density of the plasma sheet and (2) the velocity of the solar wind driving the temperature of the plasma sheet, appear to be completely unrelated, even though the solar wind density and the solar wind velocity have a strong anticorrelation. Future work is outlined.